1965
DOI: 10.1063/1.1702999
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Dislocation Theory of Crystal Plasticity. II. Easy Glide and Strain Hardening

Abstract: Mathematical descriptions of the stress-strain-time behavior of plastic crystals are developed using a statistical approach to dislocation dynamics. First, the ``easy-glide'' portions of stress-strain curves are described in terms of glide band propagation. Then, three models of strain hardening are developed and used in numerical calculations of stress-strain curves. In one model, the mean density of mobile dislocations first increases and then decreases with increasing plastic strain. In another, strain intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…It is mentioned that although the form for v might not adequately describe the dislocation motion of all solid materials [13], it is desirable to develop a model that when integrated within a multi-dimensional framework is guaranteed not to exceed a saturation level in the event of over-stress. In the model for f, taken from [12], the exponent can be varied arbitrarily to accommodate the desired non-linearity, but here we restrict the range to 0 :S: n :S: 1 to conform with the requirement that the deformations asymptote to a maximum in the limit of finite strains Cp-+ oo. Note that an alternative approach to introducing a mechanism for strain hardening proposed in [12] is to take f = 1 and modify the characteristic drag stress to be some function of the plastic strain such that the dislocation velocity increases with increasing plastic strain.…”
Section: Closure Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is mentioned that although the form for v might not adequately describe the dislocation motion of all solid materials [13], it is desirable to develop a model that when integrated within a multi-dimensional framework is guaranteed not to exceed a saturation level in the event of over-stress. In the model for f, taken from [12], the exponent can be varied arbitrarily to accommodate the desired non-linearity, but here we restrict the range to 0 :S: n :S: 1 to conform with the requirement that the deformations asymptote to a maximum in the limit of finite strains Cp-+ oo. Note that an alternative approach to introducing a mechanism for strain hardening proposed in [12] is to take f = 1 and modify the characteristic drag stress to be some function of the plastic strain such that the dislocation velocity increases with increasing plastic strain.…”
Section: Closure Modelsmentioning
confidence: 99%
“…In the model for f, taken from [12], the exponent can be varied arbitrarily to accommodate the desired non-linearity, but here we restrict the range to 0 :S: n :S: 1 to conform with the requirement that the deformations asymptote to a maximum in the limit of finite strains Cp-+ oo. Note that an alternative approach to introducing a mechanism for strain hardening proposed in [12] is to take f = 1 and modify the characteristic drag stress to be some function of the plastic strain such that the dislocation velocity increases with increasing plastic strain. This approach is taken in [24] where it is suggested that non-linear hardening can be accounted for by assuming the drag stress is a polynomial of higher order: D = P(cp)· In fact both interpretations are equivalent and choosing either makes no difference to the final form of Eq.…”
Section: Closure Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to close the model we require a equation of evolution for the dislocation densities. Processes resulting in changes in dislocation density include production by fixed sources, such as Frank-Read sources, breeding by double cross slip and pair annihilation (see [37] for a review; see also [38,39,40,41,42,43]). Although the operation of fixed FrankRead sources is quickly eclipsed by production due to cross slip at finite temperatures, it is an important mechanisms at low temperatures.…”
Section: Dislocation Evolution: Multiplication and Attritionmentioning
confidence: 99%
“…Our analytical solution, in conjunction with Franciosi's relations, completely determines the hardening relations of the crystal in terms of the density of dislocations in all slip systems. To obtain a closed set of constitutive relations, we draw on the work of Gillis and Gilman (1965) and Essmann and Rapp (1973) to formulate the requisite equations of evolution for the dislocation densities as a function of slip activity.…”
Section: Introductionmentioning
confidence: 99%